2009
DOI: 10.1111/j.1464-410x.2009.08678.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal isoproterenol reduces renal pelvic pressure during semirigid ureterorenoscopy: a porcine model

Abstract: were recorded. The increase in renal pelvic pressure was examined with increasing flow rates (0, 4, 8,12,16, 25 and 33 mL/min) with saline alone or saline + ISO 0.1 μ g/mL. Perfusion was initiated on the left side, with randomization for adding ISO or not. Thereafter perfusion was done on the right side as a control in each pig. The surgeons were unaware of whether ISO was added or not. RESULTSThe mean ( SD ) baseline pelvic pressures in the saline and ISO group were 28 (7.1) and 25 (9.8) mmHg, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…The trend of extensive pressure rises significantly decreased during isoprenalin irrigation, and the average pressure remained below the level of intrarenal back flow. Similar results were obtained in an experimental swine study showing that isoprenalin significantly reduced the pressure-flow relation during semirigid ureterorenoscopy (Jakobsen et al 2010 ).…”
Section: Discussionsupporting
confidence: 84%
“…The trend of extensive pressure rises significantly decreased during isoprenalin irrigation, and the average pressure remained below the level of intrarenal back flow. Similar results were obtained in an experimental swine study showing that isoprenalin significantly reduced the pressure-flow relation during semirigid ureterorenoscopy (Jakobsen et al 2010 ).…”
Section: Discussionsupporting
confidence: 84%
“…24 Studies demonstrated that the use of intraluminal isoproterenol could reduce pelvic pressure by relaxing ureteral tone during endoscopy. 25,26 In our study, the complete occlusive nature of the 8F balloon catheter could prevent the irrigant from flowing proximal to the balloon when it was dilated, and the balloon was deflated per 20 minutes to drain the pelvis and to reduce the intrarenal pressure to the lowest level. Only 1.92% (1/52) patients undergoing POBC-URSL had postoperative fever.…”
Section: Discussionmentioning
confidence: 88%
“…For patients who fail to place the sheaths, placing the D-J stent for 2 weeks is suggested. Secondly, although vacuum suction devices can signi cantly reduce the renal pelvic pressure [15], there is a lack of effective devices to monitor the real-time changes of the suction force and renal pelvic pressure [16]. Therefore, it is necessary for the surgeon to be experienced and to arrive at an effective judgment of the lithotripsy procedure.…”
Section: Discussionmentioning
confidence: 99%